PELATIHAN DAN PENERAPAN APLIKASI ARSIP DOKUMEN GUNA MENUNJANG PROSES BISNIS PADA KELOMPOK USAHA MENENGAH - Fransiskus Mario Hartono Tjiptabudi (Universitas Majalengka, 2022)
Document archives play an important role in managing an institution or organization, both profit-oriented and non-profit. Given the 10-year period of storing documents for an institution, it is necessary to pay attention to the right archiving method so that it can maintain the state of the document properly and is easy to find if the document is needed, for example for decision making. Along with the development of technology, documents in the form of letters, reports and various other types of documents are not only stored in hardcopy or printed formats, but are also stored in softcopy or digital formats. Digital archiving of documents is an effort made by activity partners in this case a medium enterprise group called PT. Trimitra Jaya Griya to achieve good document governance and also support the business processes that are carried out. The purpose of this activity is to produce appropriate technology in the form of computer applications that will be applied to partners followed by the installation process and also training. The result achieved is the implementation of a desktop-based document archive application (AIKO) that has obtained an IPR certificate.